436 Elucidating the role of the rete ovarii in fertility and progesterone signaling - Lillian Folts; Anthony Martinez; Wendy Zhang; Jennifer McKey (Journal of Clinical and Translational Science)
Objectives/Goals: The goal of this study is to determine the function of the rete ovarii (RO), an uncharacterized secretory epithelial appendage to the ovary. I am testing the hypothesis that the RO is critical for the maintenance of the ovarian reserve and fertility, and progesterone signaling plays a role in the function of the RO. Methods/Study Population: For this project, I am utilizing a mouse model. To visualize the rete ovarii (RO) in vivo, I am using a Pax8rtTA; TRE-H2B-Gfp (PTG) reporter mouse, which expresses green fluorescent protein in the RO. To determine the role of the RO in fertility and maintenance of the ovarian reserve, I will surgically ablate the RO or perform a sham surgery on adult female PTG mice. Then, I will follow-up with quantification of the ovarian reserve and long-term fertility tracking studies. To determine how the RO responds to progesterone, the RO will be cultured ex vivo in the presence and absence of progesterone. I will perform a morphometric analysis of the RO, as well as collect secreted proteins from the media for proteomic analysis. Results/Anticipated Results: If the RO is important for ovarian homeostasis, I expect that in the absence of the RO, ovarian functions such as maintenance of the ovarian reserve and fertility will be impaired. Additionally, because the RO expresses progesterone receptors, I anticipate that the RO will be responsive to progesterone as shown in changes in the morphometric analysis and in changes in secreted proteins in the presence of progesterone. Discussion/Significance of Impact: A major gap in knowledge regarding female physiology and reproductive health is the role of the RO. We expect this work to reveal that progesterone signaling in the RO is important for regulating ovarian functions and to show that the RO is a critical modulator of female fertility and reproductive function.